Noise prediction on ships - SZCZERBICKI, Edward; SZUWARZYŃSKI, Andrzej (Archives of Acoustics, 1981)
This paper presents the results of the first stage of investigations aimed at the development of an effective method for predicting noise on ships. The results of measurements taken on Polish ships by the Technical and Research Department of the Maritime Institute under the departmental problems 103 and 104 were used. A statistical method of multiple linear regression was used for data processing. Calculated and measured results were compared. It has been shown that statistical methods are valid for predicting noise in the accomodation in the superstructure of a ship. The direction of further research, intended to improve the method presented, is defined.